Patients’ and caregivers’ perceptions of bariatric surgery: A France and United States comparative infodemiology study using social media data mining - Czernichow, Sébastien; Rassy, Nathalie; Malaab, Joelle; Loussikian, Paul; Mebarki, Adel; Khadhar, Mickail; Poghosyan, Tigran; Fagherrazi, Guy; Carette, Claire; Schück, Stéphane; Rives-Lange, Claire (Frontiers in Digital Health, 2023)
Background People are conversing about bariatric surgery on social media, but little is known about the main themes being discussed. Objective To analyze discussions regarding bariatric surgery on social media platforms and to establish a cross-cultural comparison of posts geolocated in France and the United States. Methods Posts were retrieved between January 2015 and April 2021 from general, publicly accessed sites and health-related forums geolocated in both countries. After processing and cleaning the data, posts of patients and caregivers about bariatric surgery were identified using a supervised machine learning algorithm. Results The analysis dataset contained a total of 10,800 posts from 4,947 web users in France and 51,804 posts from 40,278 web users in the United States. In France, post-operative follow-up (n = 3,251, 30.1% of posts), healthcare pathways (n = 2,171, 20.1% of the posts), and complementary and alternative weight loss therapies (n = 1,652, 15.3% of the posts) were among the most discussed topics. In the United States, the experience with bariatric surgery (n = 11,138, 21.5% of the posts) and the role of physical activity and diet in weight-loss programs before surgery (n = 9,325, 18% of the posts) were among the most discussed topics. Conclusion Social media analysis provides a valuable toolset for clinicians to help them increase patient-centered care by integrating the patients’ and caregivers’ needs and concerns into the management of bariatric surgery.